γ-Oryzanol-Loaded PLGA nanoparticles: enhanced drug delivery and therapeutic efficacy for breast cancer therapy - Ma, Teng; Geng, Xiaoning; Shi, Weiwei; Yu, Chunli; Wu, Xuesong; Cui, Nannan; Zhao, Ze; Li, Huazhong; Zhao, Chuanliang; Ni, Qingbin; Zhu, Xiaodan; Xia, Pengcheng (Frontiers in Bioengineering and Biotechnology, 2025)
IntroductionBreast cancer treatment is plagued by systemic toxicity and drug resistance, prompting the search for better drug delivery systems, with oryzanol, a natural compound with anti-tumor potential but poor water solubility, emerging as a candidate. PLGA nanoparticles, a biodegradable and FDA-approved platform, are designed to encapsulate oryzanol, addressing its solubility issues and enabling targeted, controlled release to enhance anti-breast cancer efficacy. This study focuses on developing and characterizing γ-oryzanol-loaded PLGA (γ-oryzanol@PLGA) nanoparticles, evaluating their formulation, cellular effects, and mechanisms, intending to lay a preclinical foundation for oryzanol as a safe adjuvant therapy for breast cancer.MethodsTo address this unmet need, this study developed γ-oryzanol@PLGA nanoparticles (NPs) as a potential therapeutic strategy. Transmission electron microscopy (TEM) was used to characterize the morphology of the NPs. The colloidal stability and uniformity of nanoparticles were evaluated by measuring the polydispersity index (PDI) and zeta potential. Encapsulation efficiency and loading capacity were determined through UV-visible spectrophotometry. Flow cytometry was employed to assess the cellular uptake of the NPs compared to the free drug, and cytotoxicity assays were conducted to measure the effective concentration. Transcriptomic analysis was performed to identify differentially expressed genes and enriched cancer-related pathways.ResultsTEM results showed that the NPs were spherical with uniform morphology, with blank NPs having a size of 232.50 ± 1.27 nm and drug-loaded NPs being 241.60 ± 7.89 nm. The NPs exhibited excellent colloidal stability (PDI <0.03, zeta potential: −20 to −26 mV). Effective package load (86.22% ± 3.43%) and loading capacity (7.89% ± 0.31%) were achieved. Flow cytometry indicated a 3.2-fold enhanced cellular uptake compared to the free drug at 4 H (p < 0.05), and cytotoxicity assays showed a 3-fold reduction in the effective concentration. Transcriptomic analysis identified 576 differentially expressed genes and enriched cancer-related pathways, revealing the molecular mechanisms of the enhanced antitumor effects.ConclusionCollectively, these findings demonstrate that γ-oryzanol@PLGA NPs significantly improve drug delivery efficiency and therapeutic potency while maintaining excellent biocompatibility. This presents a promising nanoplatform for breast cancer treatment, warranting further preclinical development. Future studies should focus on in vivo validation and the exploration of combination therapies to fully realize the potential of this novel approach.